2015
DOI: 10.1653/024.098.0413
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Genetic Variation in Mexican Wild Populations ofTamarixia radiata(Hymenoptera: Eulophidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Furthermore, the previous work showed a high number of haplotypes H2 samples obtained from the northeast states of Nuevo León, and Tamaulipas and the western states of Colima and Michoacán, and H1 was only obtained from the Tamaulipas state of Mexico. These findings suggest gene flow due to the release and introduction of T. radiata between countries [61]. The high haplotype diversity and nucleotide diversity (Hd > 0.78, π > 0.24) observed in overall populations from China represent stable populations with a long evolutionary history [65], and these populations are the contributors to the nucleotide diversity of T. radiata.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the previous work showed a high number of haplotypes H2 samples obtained from the northeast states of Nuevo León, and Tamaulipas and the western states of Colima and Michoacán, and H1 was only obtained from the Tamaulipas state of Mexico. These findings suggest gene flow due to the release and introduction of T. radiata between countries [61]. The high haplotype diversity and nucleotide diversity (Hd > 0.78, π > 0.24) observed in overall populations from China represent stable populations with a long evolutionary history [65], and these populations are the contributors to the nucleotide diversity of T. radiata.…”
Section: Discussionmentioning
confidence: 86%
“…Previous research revealed that a series of complex environmental factors had significant effects on survival, parasitism, and reproduction of T. radiata. Accordingly, the highest parasitism percentage was observed in summer and the lowest in winter in Sao Paulo [61].…”
Section: Discussionmentioning
confidence: 88%
“…Although, the reason for this morphological dimorphism is unclear in parasitoids, it might be related to the functional complexity of antennae between sexes in different species. Nonetheless, regarding Eulophidae, funicular segment size was different in holotypes of P. elaeisis from different countries in South America (Delvare & Lasalle, 1993), and relevant differences in number of funicular segments and antenna size of males were found in population of T. radiata (Peña-Carrillo et al, 2015) suggesting that the size and/or number of antennomers may also vary according to geographic position in populations from the same species. Furthermore, the antennal size may be associated with sensilla number and size to enlarge the surface area of sensory receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Liberibacter asiaticus, such threshold is not applicable because studies have shown low transmission associated with a single D. citri adult [11] and even more when nymphal development occurs in healthy plants [9,13,67]. Furthermore, there are diverse natural enemies contributing to the reduction in the vector population [68][69][70][71] that would potentially and naturally assist the prevention of the vector from reaching efficient transmission levels. Hence, it is feasible to consider the use of SPRT sequential plans to support decision making in vector control.…”
Section: Discussionmentioning
confidence: 99%
“…This avoids intensive and extensive chemical control of the vector such as the program that exists in Brazil [22]. Furthermore, it would increase the opportunity for biological control [68][69][70][71]. In this manner, the current production systems could move towards the sustainable citrus industry of the future.…”
Section: Discussionmentioning
confidence: 99%